ASPEK PSIKIATRI ACNE VULGARIS - Burhanudin Ichsan; Abi Muhlisin (Jurnal Berita Ilmu Keperawatan, 2008)
Acne vulgaris is a self-limited disease, seen primarily in adolescent, involving the sebaceous follicles. Most cases of acne are pleomorphic, presenting with a variety of lesions consisting of comedones, papules, pustules, nodules. Although the basic cause of acne is unknown, there is considerable information on the various factors concerned in its pathogenesis. Acne is a multifactorial disease. One of them is psychiatry aspect. Psychotherapy and psychopharmacology should be considered in management of acne vulgaris. The holistic approach of the management is recommended.